Comparison of immediate release oral oxycodone hydrochloride(kappa 2 receptor agonist) with oral pantoprazole in the treatment of functional dyspepsia - Omar, Azaharim (2012)
Comparison of Immediate Release Oral Oxycodone Hydrochloride(Kappa 2 receptor agonist) with Oral Pantoprazole in the treatment of Functional Dyspepsia The treatment of patients with functional dyspepsia remains unsatisfactory. We assessed the efficacy and safety of Oxycodone Hydrochloride-Kappa 2 receptor agonist, in patients with functional dyspepsia. Patients with functional dyspepsia were randomly assigned to receive either Oral Oxycodone Hydrochloride 5mg pm basis and Oral Pantoprazole 40mg od. After eight weeks of treatment, three primary efficacy end points were analyzed: the change from baseline in the severity of symptoms of functional dyspepsia(as assessed by the Leeds Dyspepsia Questionnaire(LDQ)), patients' global assessment of efficacy using Global Assessment Score(GAS) (the proportion of patients poor and good improvement), and the severity of pain and bloatedness as rated by LDQ severity scale. The safety of Oxycodone Hydrochloride assessed by the presence of significant side effect. We randomly assigned 60 patients for this study. After eight weeks, overall patients in Oxycodone Hydrochloride group had marked improvement of symptoms, as compared with patients receiving Pantoprazole daily. Analysis of patients' global assessment of efficacy(GAS) also revealed that Oxycodone Hydrochloride group was significantly superior to Pantoprazole with excellent proportion of good(26 vs 1)(P value<0.001). The total LDQ symptom score improved significantly in Oxycodone Hydrochloride groups(13.00±3.29 vs 20.40±3.07)(P va!ue<0.001), with the greatest symptom-score improvement is less than 15(P<0.05). Epigastric pain and bloatedness improvement were greater in Oxycodone Hydrochloride than Pantoprazole; LDQ severity scale for epigastric pain(2.0±l vs 4.0±l) (P<0.001) and bloatedness(2.0±l vs 3.0±l) (P<0.001). The side effects of Oxycodone Hydrochloride was giddiness(13 vs 0)(P<0.001). However when comparing it amongst the Oxycodone Hydrochloride group, it was statistically insignificant(13 vs 17)(p=0.465). Oxycodone Hydrochloride significantly improves symptoms in patients with functional dyspepsia with tolerable side effects.